Augmented Lagrangian Algorithm for Hydrothermal Scheduling - Subramani, R.; Vijayalakshmi, C. (EAI Endorsed Transactions on Energy Web, 2018)
This paper mainly deals with a new algorithm for solving hydrothermal scheduling problem with transmission and environmental constraints using Augmented Lagrangian(AL) method. Hydrothermal scheduling is a most important task in power management system. Transmission capacity and environmental constraints are relaxed by using Lagrangian multipliers. The existing methods are provided suboptimal solutions from the computational burden due to the large number of variables involved in the problem. This paper ensures efficient technique that involves a reduced number of decision variables for hydrothermal scheduling to reduce the total operating cost through AL method. The ultimate aim of hydrothermal scheduling is to ensure the optimal generation in both hydro and thermal units in order to fulfill the demands over a scheduled horizon. In this paper optimal hourly schedule for power generation in hydrothermal scheduling system applying Augmented Lagrangian Relaxation (ALR) technique.